A Case of Monoclonal Lymphoplasmacytosis of the Bone Marrow with IgM-Positive Russell Bodies. (19th January 2011) - Kayano, Hidekazu; Shimada, Tsuneyuki; Wakimoto, Naoki; Nakamura, Yuichi; Bessho, Masami; Yamaguchi, Hiroshi; Sasaki, Atsushi; Shimizu, Michio
Abstract : A 71-year-old Japanese male patient infected with HCV was diagnosed with thrombocytopenia. Histological examination of the bone marrow aspirate showed numerous lymphoid aggregates with Russell bodies. Immunohistochemistry and flow cytometric analysis demonstrated clonal expansion of CD5+ CD23+ B cells. Russell bodies were positive for IgM and lambda immunoglobulin light chain. The patient also underwent gastric biopsy, which revealed Helicobacter pylori (HP) infection. Subsequent eradication of the bacteria resulted in improvement of his thrombocytopenia. The clinical course remained uneventful at 15-month follow-up, consistent with monoclonal B-cell lymphocytosis. The observed clonal expansion with plasmacytic differentiation may have occurred under the influence of HCV with HP infection.